Efficacy and safety of regorafenib dose-escalation therapy for Japanese patients with refractory metastatic colorectal cancer (RECC study) - Ishiyama, Shun; Yamada, Takeshi; Nakamura, Masato; Enomoto, Masanobu; Sugimoto, Kiichi; Yokomizo, Hajime; Kosugi, Chihiro; Ohta, Ryo; Ishimaru, Kei; Sonoda, Hiromichi; Ishibashi, Keiichiro; Kuramochi, Hidekazu; et al. (International journal of clinical oncology, 2022)
Background Regorafenib significantly improves overall survival in previously treated metastatic colorectal cancer patients. However, various toxicities, such as hand-foot skin reaction (HFSR), fatigue, and liver dysfunction have limited the use of regorafenib. These toxicities appear soon after treatment initiation. The ReDOS study demonstrated the effectiveness of a weekly dose-escalation therapy of regorafenib starting with a lower daily dose; however, its usefulness in Asian subjects is unknown. We conducted a phase II study to evaluate the safety and survival benefit of regorafenib dose-escalation therapy for Japanese patients. Methods Patients with sufficient organ function, who had previously received more than two lines of chemotherapy were included. Regorafenib was started at 80 mg/day and escalated to 120 mg/day in Week 2 and 160 mg/day in Week 3, if no severe drug-related toxicities were observed. The primary endpoint was cancer progression-free survival (PFS). Tumor response and progression were assessed radiologically every 8 weeks. This study was registered in the University Hospital Medical Information Network (UMIN#UMIN000028933). Results 57 patients were enrolled and all started regorafenib at 80 mg/day. 32 patients (56.1%) were subsequently escalated to 120 mg/day and 19 (33.3%) to 160 mg/day. Only 8 patients (14.0%) discontinued treatment because of adverse events. Median PFS was 1.9 months. Median overall survival was 8.9 months, the response rate was 0%, and the disease control rate was 31.6%. The most frequent adverse event greater than grade 3 was hypertension (19.3%), followed by HFSR (14.0%). Conclusions Regorafenib dose-escalation therapy is well tolerated with PFS-like regorafenib standard therapy.